Influence of triethanolamine on the chemical bath deposited NiS thin films - Kassim, Anuar; Ho, Soon Min; Tan, Wee Tee; Ngai, Chee Fei (Science Publications, 2011)
Problem statement: Recently, many scientists looking for new chalcogenide materials for the solar cell applications. Nowadays, silicon-based solar cell became dominant products in the market. Because of expensive silicon-based solar cells, scientists hope replaces it with cheaper chalcogenide materials. Approach: The binary chalcogenide materials were deposited onto microscope glass slide using simple chemical bath deposition method. Here, we study the influence of complexing agent in the preparation of thin films. The structural and morphological of the deposited films have been studied using X-ray diffraction and scanning electron microscopy, respectively. Results: The X-ray diffraction data showed that the films had polycrystalline in nature with hexagonal structure. The films deposited using 0.1 M of triethanolamine showed more NiS peaks and larger grain sizes as compared with 0.05M and 0.2 M triethanolamine based on the X-ray diffraction and scanning electron microscopy analysis, respectively. Conclusion: The complexing agent played important role during the deposition process.